A Single‐Pixel RGB Device in a Colorful Alphanumeric Electrofluorochromic Display. Issue 37 (2nd August 2020) - Zhang, Weiran; Zhang, Yu‐Mo; Xie, Fuli; Jin, Xuchao; Li, Jing; Yang, Guojian; Gu, Chang; Wang, Yuyang; Zhang, Sean Xiao‐An
Abstract: With the rapid development of human society, consumer electronics have brought marvelous changes to human daily life, but they are accompanied by the much higher demand of display quality and visual experience. Therefore, ideal conversion among the three primary colors—red (R), green (G), and blue (B)—in a single pixel has been a better way to avoid the insurmountable technical barrier of subpixel technology of modern displays. Electrofluorochromic (EFC) materials capable of a novel luminescent switching, open a powerful way to design optoelectronic devices for displays and information storage etc. Colorful EFC devices, especially emitting the ideal three primary colors without subpixel technology, have been a challenge for years. Herein, a long‐awaited single‐pixel device with RGB color is fabricated successfully based on proton‐coupled electron transfer. The RGB EFC device exhibits outstanding EFC properties, such as low turn‐on voltage (+1.0 and −1.0 V), large color gamut, and good stability (500 cycles for each color). Prototypes of colorful alphanumeric displays are well demonstrated in a facile way. The success of this new exploration of single‐pixel RGB EFC device not only provides the possibility of full‐color emission in EFC devices, but also will widely broaden the EFC system and their applications. Abstract : A single‐pixel RGB electrofluorochromic (EFC) device is fabricated based on proton‐coupled electron transfer, with remarkable EFC properties, and a prototype of a colorful pixel‐based alphanumeric display is demonstrated. The success of this new exploration provides the possibility of full‐color emission in EFC devices, and widely broadens the EFC system and its applications.